Collaborative Governance in Police: A Review of Research, Managerial Implication and Agenda for Future Research - Batara Indra Aditya; Retno Kusumastuti (Borong Newinera Publisher, 2023)
This study aims to systematically review research related to collaborative governance. This study also aims to discuss the scientific contributions of previous research related to the dimensions, antecedents and consequences of collaborative governance. Furthermore, this study conducted a search of the Scopus database related to collaborative governance published from 2009 to 2023Through the screening process, we found 45 relevant articles that could be sampled from a total of 798 articles found during the initial search. The results showed that collaborative governance is a collaborative concept that is important for organizations in achieving organizational goals, these findings also show the dimensions, antecedents and consequences of collaborative governance.